The broken dice, and other mathematical tales of chance - Ekeland, I. (Ivar), 1944- (Chicago : University of Chicago Press, 1993)
Explains the cultural implications of recent mathematical theories, focusing on chance and probability.
Translation of: Au hasard.
Includes bibliographical references and index.
Adult
Keywords: Mathematical statistics; Probabilities; Mathematics; Probabilities; Statistics